2016
DOI: 10.5799/ahinjs.01.2016.02.0595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single Intravitreal Ranibizumab Injection on Diabetic Macular Edema in Patients Who Discontinued Treatment

Abstract: Objective: To evaluate the effect of a single dose of ranibizumab in patients with diabetic macular edema who discontinued treatment. Methods: One eye of 85 patients with diabetic macular edema who discontinued treatment after a single injection of ranibizumab was studied. Best corrected visual acuity (BCVA), intraocular pressure (IOP), central macular thickness (CMT), and optical coherence tomography imaging were evaluated retrospectively. Changes in BCVA, IOP, CMT, and their correlations with the follow-up p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This result was similar to earlier studies. (Yumusak et al, 2016). The AS examination showed that on the day of injection, 26 patients developed suprachoroidal haemorrhage (SCH), but on day 7, 0 patients developed SCH because it is a selflimiting condition.…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to earlier studies. (Yumusak et al, 2016). The AS examination showed that on the day of injection, 26 patients developed suprachoroidal haemorrhage (SCH), but on day 7, 0 patients developed SCH because it is a selflimiting condition.…”
Section: Discussionmentioning
confidence: 99%